After Diu: The Forgotten Islamic Trade in Early Nineteenth Century Cantonese Confucian Historiography (After Diu: Perdagangan Islam yand Kian dilupakan pada Awal Abad kesembilan belas Historiografi Cantonese Confucioan) - 孔德維 HUNG Tak Wai (Journal of Islam in Asia (E-ISSN 2289-8077), 2019)
Since the early 20th century, historians have studied interactions between China and Islamic communities. Most of them focused on the prosperity brought by the maritime trade between Muslims and Chinese in the earlier eras. How this trade ended, however, has not been extensively studied. This article studies the narratives regarding Arabs and Muslims participating in the Canton trade, as recorded in Yuehai guanzhi粵海關志 [Gazetteer of Canton Customs]. Yuehai guanzhi was published by Liang Tingnan 梁廷枏 (1796–1861), a Cantonese Confucian elite, with the first-hand government records in 1838, by which time non-Chinese speaking Muslim merchants had already became rare in the region. This article investigates how Islamic trade was recorded during the early 19th century. In particular, it will illustrate how the trade ended and was forgotten due to the diminishing presence of Muslim merchants after the Battle of Diu in 1509. Keywords: Chinese Islam, Canton trade, customs system, Yuehai guanzhi, Leung Tingnan. Abstrak Sejak awal abad ke-20, sejarawan telah mengkaji interaksi yang berlaku antara komuniti Cina dan Islam. Kebanyakan mereka memberi tumpuan terhadap kemasyhuran perdagangan maritim antara Muslim dan Cina pada era tersebut. Walau bagaimanapun, kisah berakhirnya perdagangan ini tidak dikaji secara meluas oleh para sejarawan. Artikel ini mengkaji naratif mengenai orang Arab dan Muslim yang terlibat dalam perdagangan Canton, seperti yang dicatatkan dalam Yuehai guanzhi 粵 海關 志 [Gazetteer of Canton Customs]. Yuehai guanzhi telah diterbitkan oleh Liang See 梁廷 枏 (1796-1861), seorang elit Confucian Kantonis, dengan menggunakan rekod pertama kerajaan pada tahun 1838, dimana ketika itu para peniaga Muslim yang tidak fasih berbahasa Cina telah menjadi asing di rantau ini. Artikel ini mengkaji bagaimana perdagangan Islam direkodkan pada awal abad ke-19. Secara khususnya, artikel ini menggambarkan bagaimana perdagangan maritim antara Muslim dan Cina berakhir dan dilupakan setelah berkurangnya jumlah pedagang-pedagang Muslim selepas Pertempuran Diu pada tahun 1509. Kata Kunci: Cina muslim,canton trade, sistem budaya, Yuehai guanzhi Leung Tingnan.